COVID-19 and the cardiovascular system - Zheng, Ying-Ying; Ma, Yi-Tong; Zhang, Jin-Ying; Xie, Xiang (Nature reviews cardiology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infects host cells through ACE2 receptors, leading to coronavirus disease (COVID-19)-related pneumonia, while also causing acute myocardial injury and chronic damage to the cardiovascular system. Therefore, particular attention should be given to cardiovascular protection during treatment for COVID-19.